2022
DOI: 10.1021/acs.est.2c03762
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Production of Carbon Monoxide from Dissolved Organic Matter: Role of Lignin Methoxyarene Functional Groups

Abstract: Carbon monoxide (CO) is the second most abundant identified product of dissolved organic matter (DOM) photodegradation after CO 2 , but its formation mechanism remains unknown. Previous work showed that aqueous photodegradation of methoxy-substituted aromatics (ArOCH 3 ) produces CO considerably more efficiently than aromatic carbonyls. Following on this precedent, we propose that the methoxy aromatic groups of lignin act as the C source for the photochemical forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…Product 2 might undergo elimination reactions, resulting in the loss of either formaldehyde (HCHO) or acetaldehyde (CH 3 CHO), leading to product 3 (MW = 192 g mol –1 ) appearing as m / z = 162 ([P 3 − CO] + ) or 4 (MW = 206 g mol –1 ) appearing as m / z = 162 ([P 4 − CO] + ), respectively. Recent studies also showed that the aromatic methoxy group produced CO after UV irradiation with conversion efficiency up to 17.6% . Further experiments with MACR in the presence of DMB were performed, but no product peak appeared within 3 h of irradiation time (Figure S13 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Product 2 might undergo elimination reactions, resulting in the loss of either formaldehyde (HCHO) or acetaldehyde (CH 3 CHO), leading to product 3 (MW = 192 g mol –1 ) appearing as m / z = 162 ([P 3 − CO] + ) or 4 (MW = 206 g mol –1 ) appearing as m / z = 162 ([P 4 − CO] + ), respectively. Recent studies also showed that the aromatic methoxy group produced CO after UV irradiation with conversion efficiency up to 17.6% . Further experiments with MACR in the presence of DMB were performed, but no product peak appeared within 3 h of irradiation time (Figure S13 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
“…Recent studies also showed that the aromatic methoxy group produced CO after UV irradiation with conversion efficiency up to 17.6%. 97 Further experiments with MACR in the presence of DMB were performed, but no product peak appeared within 3 h of irradiation time (Figure S13 in the Supporting Information). It should be mentioned that the UPLC/ESI(+)-MS method used fails to measure formaldehyde or acetaldehyde.…”
Section: Kinetics Of Excited Triplet-state Photosensitizersmentioning
confidence: 99%
“…Recently, Ossola et al. (2022) demonstrated for the first time a precise mechanism for CO production by CDOM photolysis based on the study of Stubbins et al. (2008).…”
Section: Resultsmentioning
confidence: 99%
“…CO and CO 2 are the key oxidation products supporting a photomineralization mechanism and a decrease in TOC with UVB irradiation. 5,71 These end products were quantified using a GC-FID setup, and samples analyzed were the second and third batch of (NH 4 ) 2 SO 4 -methylglyoxal, the December sample for firewood smoke and the Padua Friday sample. SRFA results are reported in Borduas-Dedekind et al 5 In (NH 4 ) 2 SO 4 -methylglyoxal solutions, CO 2 concentrations increased on average by 762 μM (Figure 5).…”
Section: Photoproductsmentioning
confidence: 99%